2016
DOI: 10.1186/s12885-016-2426-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breast cancer biological subtyping on tumor size assessment by ultrasound and mammography - a retrospective multicenter cohort study of 6543 primary breast cancer patients

Abstract: BackgroundMammography and ultrasound are the gold standard imaging techniques for preoperative assessment and for monitoring the efficacy of neoadjuvant chemotherapy in breast cancer. Maximum accuracy in predicting pathological tumor size non-invasively is critical for individualized therapy and surgical planning. We therefore aimed to assess the accuracy of tumor size measurement by ultrasound and mammography in a multicentered health services research study.MethodsWe retrospectively analyzed data from 6543 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 15 publications
6
14
2
Order By: Relevance
“…A total of 15 patients with three common tumor subtypes were assessed. The majority of patients had metastatic disease at diagnosis and the median OS observed in the respective cancer subtypes was in line with previously published cohorts (42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 89%
“…A total of 15 patients with three common tumor subtypes were assessed. The majority of patients had metastatic disease at diagnosis and the median OS observed in the respective cancer subtypes was in line with previously published cohorts (42)(43)(44)(45)(46).…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, it was reported that the tumor size, patient age, and nodal status were significantly associated with the biological characteristics of tumors . For instance, a tumor size larger than 2 cm was more common in human epidermal growth factor receptor 2 and triple‐negative subtypes of IBC; patients younger than 50 years showed more hormone receptor–negative cancers compared with older patients; and nodal metastases were more frequent in patients with the human epidermal growth factor receptor 2 subtype . Therefore, when evaluating the biological properties of tumors, these preoperative clinical parameters should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…4c). This may be because screening mammography detects relatively small primary breast tumors (<2 cm) 45 . However, even after normalization to primary tumor age (namely ts/T), which depends on tumor size and the underlying growth parameters (Supplementary Note), breast cancer was found to disseminate later than colorectal and lung cancers ( Fig.…”
Section: Chronology Of Metastatic Seedingmentioning
confidence: 99%